A autoria nas produções de crônicas da Olimpíada da Língua Portuguesa : um olhar enunciativo-discursivo - Barros, Leila Figueiredo de (2012)
This present paper aims to show our research Masters, as investigation about the authorship in the book produced by students in the elementary school in the third grade and freshman from High School project participants in the Olympics Portuguese Language Writing the Future (OLPEF). For this achievement, we selected the teacher's Notebook "The occasion is the writer, " the second edition of 2010 in order to analyze qualitatively the theoretical and methodological base taken as didactic model of gender and chronic discusses how this model and shows the discourse, and a corpus from ten finalists chronicles produced by students who participated in the project. The Olympic is originated from Writing the Future program, developed by Itaú a Social Foundation between 2002 and 2006. Currently, it is a partnership of the Ministry of Education with the Itaú Social Foundation and the Center for Studies and Research in Education, Culture and Community Action (Cenpec).The activities from the project of the Olympics occur in different ways because, in odd years, there are teacher training and, in even, is holding a competition to produce texts with students from public schools in entire country, whose poems are selected genres, memories literature, essays and opinion pieces. In this context, we consider as relevant to examine how the material of the Portuguese Language Olympic forwards the teaching project for the chronic gender, as a genre studying a hybrid of social nature and see how it allows the social aspects relate to highly complex from the natural look is relevant to everyday school practices, and represents a study of alternative learning the tools that have been received by the schools lately. Our thoughts and analyzes are grounded in the theory of enunciative-discursive socio-historical approach of the Bakhtin circle (1919.1924, 1929, 1952-1953) and teaching-learning theory of Vygotsky (1934). Besides this, we present a brief review on the production of texts for understand the process of didactization from the text in Portuguese language classes and some concepts of the Geneva school. Under the light of the enunciative-discursive theory, we search to understand, one side, the didactic material for the chronicle, for the purpose of this material is to form a student author for this genre and on the other side, the discourse in the book so in this way we could observe how students established themselves as real authors. In our analysis, we found that the Book of the Olympics dialogue with the official (PCNLP, OCEM, MEC) and the activities do not give the students enough training to be a subject-author of chronic. This gap could be observed in production, because, by analyzing the productions, students could not be authors of literary chronicle, but many texts, setting from other genres. We also conclude that the material has been focused on the genre as a literary chronicle, however, we believe that the discursive approach can provide students a broader view about the disease, as an object from discourse, that is multifaceted, because of its hybrid nature and giving more opportunities and training to students.